Respuesta :

Answer:

(12, - 1 )

Step-by-step explanation:

Given the 2 equations

x + 4y = 8 → (1)

2x - 5y = 29 → (2)

Rearrange (1), expressing x in terms of y by subtracting 4y from both sides

x = 8 - 4y → (3)

Substitute x = 8 - 4y into (2)

2(8 - 4y) - 5y = 29 ← distribute and simplify left side

16 - 8y - 5y = 29

16 - 13y = 29 ( subtract 16 from both sides )

- 13y = 13 ( divide both sides by - 13 )

y = - 1

Substitute y = - 1 into (3) for corresponding value of x

x = 8 - 4(- 1) = 8 + 4 = 12

solution is (12, - 1 )

[tex]x = 8 - 4y \: \: eqn \: 1[/tex]

now in eqn 2

[tex]2(8 - 4y) - 5y = 29[/tex]

[tex]16 - 8y - 5y = 29[/tex]

[tex]16 - 13y = 29[/tex]

[tex]16 - 29 = 13y[/tex]

[tex]13 = 13y[/tex]

[tex] \frac{13}{13} = y[/tex]

[tex]y = 1[/tex]

Now in eqn 1

[tex]x = 8 - 4y[/tex]

[tex]x = 8 - 4 \times 1[/tex]

[tex]x = 8 - 4[/tex]

[tex]x = 4[/tex]

therefore x=4 & y=1 answer